Dysfunctional tear syndrome: dry eye disease and associated tear film disorders – new strategies for diagnosis and treatment. (January 2017) - Milner, Mark S.; Beckman, Kenneth A.; Luchs, Jodi I.; Allen, Quentin B.; Awdeh, Richard M.; Berdahl, John; Boland, Thomas S.; Buznego, Carlos; Gira, Joseph P.; Goldberg, Damien F.; Goldman, David; Goyal, Raj K.; et al.
Abstract : Dysfunctional tear syndrome (DTS) is a common and complex condition affecting the ocular surface. The health and normal functioning of the ocular surface is dependent on a stable and sufficient tear film. Clinician awareness of conditions affecting the ocular surface has increased in recent years because of expanded research and the publication of diagnosis and treatment guidelines pertaining to disorders resulting in DTS, including the Delphi panel treatment recommendations for DTS (2006), the International Dry Eye Workshop (DEWS) (2007), the Meibomian Gland Dysfunction (MGD) Workshop (2011), and the updated Preferred Practice Pattern guidelines from the American Academy of Ophthalmology pertaining to dry eye and blepharitis (2013). Since the publication of the existing guidelines, new diagnostic techniques and treatment options that provide an opportunity for better management of patients have become available. Clinicians are now able to access a wealth of information that can help them obtain a differential diagnosis and treatment approach for patients presenting with DTS. This review provides a practical and directed approach to the diagnosis and treatment of patients with DTS, emphasizing treatment that is tailored to the specific disease subtype as well as the severity of the condition.